Pengaruh Dosis Pupuk Urea terhadap Kandungan N Tanah, Serapan N dan Hasil Umbi Bawang Merah pada Tanah Steril dan Tanah Inokulasi - Ratih Kurniasih; Arif Wibowo; Sri Nuryani Hidayah Utami (Jurnal Pertanian Presisi (Journal of Precision Agriculture), 2017)
Fusarium wilt of shallot is caused by Fusarium solani could affect yield on shallot planting. This research was conducted to study the effect of  addition urea fertilizer on total nitrogen of soil, ammonium, nitrate, nitrogen uptake of foliage and bulbs, and bulbs yield of shallot. This research was conducted at KP4 Kalitirto Berbah and Faculty of  Agriculture, Gadjah Mada University with Randomized Complete Block Design (RCBD) with 2 factors and 4 replications. The first factor was two type of soil which were inoculated soil by Fusarium solani inoculums and sterilized soil by heating  treatment at more than 100 °C at least 3 hours. The second factor was five different dose of urea and KCl fertilizer on percentage (0, 50, 100, 150 and 200) from fertilizer recommendation. The result showed that total nitrogen of soil, ammonium, nitrate in inoculated soil lower  compared to sterilized soil. There is a positive and significant correlation between ammonium and total nitrogen of soil to fresh weight of bulb, the number of bulb and nitrogen uptake of foliage. Likewise, the fresh weight of bulbs and the number of bulb has a positive and highly significant correlation with nitrogen uptake of foliage and nitrogen uptake of bulb.